DETERMINAN PROFITABILITAS DENGAN NON PERFORMING FINANCING (NPF) SEBAGAI VARIABEL MODERASI PADA BANK MUAMALAT INDONESIA PERIODE TAHUN 2015–2022 - Larasati, Dwi Ananda; Muslihati; Nasri Katman, Muhammad (Program Studi Ekonomi Syariah, 2024)
This study of this research is to determine the effect of Mudharabah, Musyarakah and Murabahah financing on profitability at Bank Muamalat Indonesia. Apart from that, this research also aims to test whether the Non Performing Financing variable is able to moderate the relationship between each. Mudharabah, Musyarakah and Murabahah variable on Profitability at Bank Muamalat Indonesia. The data collection method in this research uses secondary data sourced from Bank Muamalat Indonesia's quarterly financial report data for the 2015-2022 period. In carrying out data analysis, the author uses analytical methods and uses the Smart PLS analysis tool. The results of this research are that mudharabah, musyarakah and murabahah financing do not have a significant effect on profitability. The results of the moderating variable show that Non-Performing Financing is able to moderate the effect of mudharabah financing on profitability at Bank Muamalat Indonesia